Implementation Of Flipped Learning-Based Learning In The Subject Of PJOK At Junior High School 3 Kartasura - Fajriansyah, Muhammad Sulthon; Agam Akhmad Syaukani; Vera Septi Sistiasih (UNIB Press, 2025)
This study explores the implementation of the Flipped Learning model in Physical Education, Sports, and Health (PJOK) at Junior High School 3 Kartasura. Flipped Learning reverses the traditional approach by having students study materials independently at home via digital media, such as videos or e-books, and then engage in practice and discussion during classroom sessions. Using a descriptive qualitative method, data were collected through interviews with the PJOK teacher, the vice principal for curriculum, and 20 students. The findings indicate that Flipped Learning was implemented effectively, with positive responses from both teachers and students. Classroom time was utilized more efficiently for practical activities, and students felt better prepared and more engaged. Challenges included limited internet access and some students’ lack of discipline in completing pre-class learning. Nevertheless, support from the school, including technological facilities, teacher training, and students’ digital literacy, facilitated success. Overall, Flipped Learning enhanced engagement, learning efficiency, and practical performance in PJOK.